2018
DOI: 10.1039/c8ta00281a
|View full text |Cite
|
Sign up to set email alerts
|

Nature inspired cathodes using high-density carbon papers with an eddy current effect for high-rate performance lithium–air batteries

Abstract: The patterned cathode exhibits improved high-rate performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…It was also found that the Pt/RuO 2 @ACT O 2 -electrode achieved at least 40 cycles in the Li-O 2 batteries without unwanted irreversible reactions. 59…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that the Pt/RuO 2 @ACT O 2 -electrode achieved at least 40 cycles in the Li-O 2 batteries without unwanted irreversible reactions. 59…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure 2 d, the decomposition of Li 2 O 2 occurs via the OER in another two-step process [ 40 ]: (1) Li 2 O 2 releases one electron and decomposes to LiO 2 and (2) LiO 2 interacts with oxygen vacancies to release the second electron and lithium ions. As a result, LOB operation completely relies on the OER and ORR during the electrochemical charge–discharge process [ 41 , 42 , 43 ].…”
Section: Basic Principles Of Li–o 2 Batteriesmentioning
confidence: 99%
“…Carbon materials generally possess many merits such as excellent electrical conductivity, good chemical and thermal stability, light weight, high surface area, sufficient resources, and low cost [41,42]. As a result, various carbon materials, including activated carbon [43], carbon paper [44,45], carbon nanotubes (CNT) [46][47][48][49], graphene [42,[50][51][52][53][54], and mesoporous carbon [55][56][57][58], have been used as the positive electrode for Li-O 2 batteries. In this section, various strategies to design high-performance carbon positive-electrode catalysts are discussed, including structural design, heteroatom doping, defect modification, and synergy of the above three strategies.…”
Section: Carbonmentioning
confidence: 99%
“…Inspired by eddy current effects in nature, Bae and co-workers [44] used an imprinting process with a micro-scale metal mold to prepare patterned carbon papers as air electrodes of Li-O 2 batteries. The patterned positive electrode not only enhanced the transport velocity of oxygen due to the intensified eddy current effect, but also increased reaction active sites due to a larger roughness factor (Figure 2a).…”
Section: Structural Designmentioning
confidence: 99%